The Effect of Instagram Unsolicited Advertisements on Consumers Buying Decision: Evidence From Youth in Dar Es Salaam - Eunice Frank Nyange (International Journal of Business, Economics, and Social Development, 2026)
This study examines the influence of unsolicited advertisements on Instagram on consumers’ buying decisions, with a particularfocus on youth in Dar es Salaam, Tanzania. The rapid growth of Instagram as a visual and interactive social media platform hastransformed it into a key marketing channel, where users are frequently exposed to unsolicited promotional content. Using anexplanatory research design, the study integrates both quantitative and qualitative approaches. Primary data were collected from 75respondents through structured questionnaires and interviews, while secondary data were obtained through desk reviews.Descriptive analysis, supported by content analysis, was employed to interpret the findings. The results indicate that Instagramplays a significant role in shaping purchasing behavior among youth, with approximately 80% of respondents reporting that theyhave accessed goods or services through the platform. Sponsored advertisements and Reels emerged as the most dominant formsof unsolicited ads. In terms of content, business-oriented advertisements accounted for the largest proportion (44%), followed byentertainment content (36%), which strongly influences emotional engagement and purchase intention. Other content categories,including affective, modeling, health and wellness, and educational advertisements, showed relatively lower influence. The findingsfurther reveal that while unsolicited ads enhance product visibility and stimulate purchasing decisions, concerns remain regardingmisleading information and consumer protection. The study contributes theoretically by applying the AIDA Model and SocialMedia Theory to explain how unsolicited advertisements attract attention, stimulate interest, create desire, and ultimately driveaction within a digital environment. Practically, the findings provide insights for policymakers, platform regulators, and marketerson improving transparency, ethical advertising practices, and effective digital marketing strategies. Overall, the study underscoresthe growing impact of unsolicited Instagram advertisements on youth purchasing decisions in emerging economies.